2022
DOI: 10.1002/phar.2708
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of NSAID‐Induced adverse events with concomitant use of misoprostol (MICRO study)

Abstract: Background Non‐steroidal anti‐inflammatory drugs (NSAIDs) are one of the most frequently used medications for pain, even though they increase the risk for adverse cardiovascular events. Objectives The objective of this study was to determine cardiovascular, cerebrovascular, and renal event rates between NSAIDs versus NSAIDs plus misoprostol. Methods A population‐based historical cohort of U.S. veterans receiving prescription NSAIDs (1,681,609) versus NSAIDs plus misoprostol (5972 misoprostol users) was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…38 Furthermore, in veteran patients in the USA who received NSAIDs, the risks of cardiovascular events, cerebrovascular events and kidney injuries were reduced by 10-40% when coadministered with misoprostol. 9 These findings are in line with those of the present study. It is worth noting that kidney injury was assessed in 3 studies based on an increase in the serum creatinine level and in 1 study based on mild renal insufficiency.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…38 Furthermore, in veteran patients in the USA who received NSAIDs, the risks of cardiovascular events, cerebrovascular events and kidney injuries were reduced by 10-40% when coadministered with misoprostol. 9 These findings are in line with those of the present study. It is worth noting that kidney injury was assessed in 3 studies based on an increase in the serum creatinine level and in 1 study based on mild renal insufficiency.…”
Section: Discussionsupporting
confidence: 93%
“…One double‐blind crossover trial found that misoprostol prevented diclofenac‐induced increases in mean arterial pressure and decreases in glomerular filtration rate, suggesting that misoprostol may prevent NSAID‐induced elevation in blood pressure and renal vasoconstriction 38 . Furthermore, in veteran patients in the USA who received NSAIDs, the risks of cardiovascular events, cerebrovascular events and kidney injuries were reduced by 10–40% when coadministered with misoprostol 9 . These findings are in line with those of the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, intake of ibuprofen (600 mg) 1 hour before the use of misoprostol could be helpful in reducing both fever and abdominal pain [28] . Previous reports also indicated that ibuprofen (600 mg) could be taken every eight hours in severe cases to avoid high temperature and abdominal pain [29][30][31] . In addition, since misoprostol was a prostaglandin E1 analogue, it might have bene ts in relieving gastric or duodenal ulcers [32,33] .…”
Section: Discussionmentioning
confidence: 99%